Systemic meningococcal infection in children of the Arkhangelsk region: predictors of unfavorable course and outcome during different periods of observation - O. V. Samodova; T. A. Gordienko; L. V. Ivanova; E. A. Krieger (Журнал инфектологии)
Invasive meningococcal infection remains a leading cause of death among infectious diseases in children.Aim. to investigate predictors of death in patients with invasive meningococcal infection during two periods of observation: 1991–2011 and 2012–2022.Materials and methods. A retrospective cohort study was conducted including 143 children aged 1,5 months to 17 years old, living in the Arkhangelsk region and having had invasive meningococcal infection. The study included two periods: 1991–2011 (N=93) and 2012–2022 (N=50). Groups of recovered and deceased patients were compared.Results. When admitted to the hospital meningococcal infection or bacterial meningitis was diagnosed in 25,5% of cases among deceased patients, and in 57,3% among survivors. More than half of the patients with an fatal outcome were not referred to the hospital after the first examination by a medical professional, unlike the recovered patients, of whom 68,8% were immediately referred to the hospital after examination. The majority of the recovered patients (82.3%) were transported to medical facilities providing specialized medical care. In the deceased group, treatment was initiated in non-specialized medical facilities in 74,5% of cases due to the distance from the regional center, where specialized care is provided. Throughout the observation period, the probability of death was higher in infants, patients with of septic shock, leukopenia, in cases requiring repeated visits by medical professional, and during initial therapy in nonspecialized medical organizations. Conclusion. The need to repeatedly seek healthcare, a different referral diagnosis, delays in receiving specialized medical care and the necessity for evacuation to the regional center for specialized care, all increase the probability of death and justify the advisability of specific prevention of meningococcal infection.